Utilization of cervical cancer screening program and its predictors in the universal health coverage era in Badung District, Bali - Wati, Putu Ayu; Januraga, Pande Putu; Putri, Wayan Citra Wulan Sucipta (Universitas Udayana, 2021)
Background and purpose: Cervical cancer is the second most prevalent cancer in women after breast cancer. Nationally, the coverage of cervical cancer screening among reproductive age women from 2014 to 2018 only reached 7.34%, while in Badung District was 10.3% in 2018. In the era of the Universal Health Coverage (UHC) schemes, cervical cancer screening has been covered. This study aims to explore factors associated with the utilization of cervical cancer screening programs in the UHC era in Badung District. Methods: This cross-sectional study was conducted from January-February 2020, involving 195 women aged 20-50 years who were selected through multistage random sampling from two villages in the Badung District. Characteristics of the women, perceptions of seriousness, vulnerability, barriers and benefits, self-efficacy, cues to action and knowledge on cervical cancer screening programs were assessed. Data was analyzed descriptively, and association was assessed with Chi square and multiple logistic regression. Results: The proportion of reproductive age women who utilized cervical cancer screening program in the last 5 years was 44.1%. The utilization of cervical cancer screening program was associated with age (AOR=0.03; 95%CI: 0.03-0.300), perceived vulnerability (AOR=28.77; 95%CI: 3.745-221.68), perceived barriers (AOR=55.70; 95%CI: 7.12-435.72), selfefficacy (AOR=34.44; 95%CI: 4.34-273.66), cues to action (AOR=19.56; 95%CI: 3.32-115.24). Conclusion: The perception of barriers was found to be significantly associated with the use of cervical cancer screening programs along with other variables related to the Health Belief Model (HBM). Structured campaigns and improvement of the quality of services should be carried out in order to increase access of women to cervical cancer screening.